Impedance Matching Method in Two-Stage Converters for Single Phase PV-Grid System - L. Heru Pratomo; F. Danang Wijaya; Eka Firmansyah (International Journal of Electrical and Computer Engineering (IJECE), 2015)
This paper presents the study on the impedance matching method in two-stage converters for single phase PV-grid system. The use of PV systems was to obtain the electrical power from the sunlight energy. The system consisted of a Buck-Boost DC-DC converter and a five-level inverter. A Buck-Boost DC-DC converter was used as a means of impedance matching to obtain the maximum power that, in this case, through a method by using the incremental conductance current control algorithm. Meanwhile a five-level inverter was used as an interface to the utilities.  By using this technique, the system came to be simple. The impedance of the power grid, a Buck-Boost DC-DC converter, and a five-level inverter were seen by PV mostly in the area of RMPP, enabling the maximum power produced by the PV to be delivered to the grid. To demonstrate the effectiveness of the design, the analysis and simulation results, furthermore, were provided